Dynamic measurement by multi-point laser Doppler vibrometer - Chang, Haoming. (2013)
A vibration measurement of a cantilever beam using a multi-point laser Doppler vibrometer (LDV) with single detector is conducted in this dissertation. Predecessors’ works towards multi-point LDV are discussed and some fundamental theories relevant to the working principles of the single point LDV and multi-point LDV are introduced. A computer simulation of the vibrating cantilever beam is conducted using finite element method with harmonic analysis techniques to study the possible vibration form that may present in the experiment. The simultaneous detection by a multi-point LDV can be extracted by the multi-point LDV by elaborately designing the central frequencies of each channel. The results from experiment and computation are compared and coincide well. Comparisons are discussed thereafter. A conclusion and the potential aspects of improvement are given at the end.